2009
DOI: 10.1080/15287390802706405
|View full text |Cite
|
Sign up to set email alerts
|

CatecholO-Methyltransferase (COMT)VAL158METFunctional Polymorphism, Dental Mercury Exposure, and Self-Reported Symptoms and Mood

Abstract: Associations were evaluated between a functional single nucleotide polymorphism (Val158Met) in the gene encoding the catecholamine catabolic enzyme catechol O-methyltransferase (COMT), dental mercury exposure, and self-reported symptoms and mood among 183 male dentists and 213 female dental assistants. Self-reported symptoms, mood, and detailed work histories were obtained by computerized questionnaire. Spot urine samples were collected and analyzed for mercury concentrations to evaluate recent exposures, wher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 42 publications
1
21
0
1
Order By: Relevance
“…Several GSH-related enzymes are highly polymorphic, and epidemiological studies demonstrated that these polymorphisms may affect the metabolism of Hg (Goyer and Clarkson 2001;Gundacker et al 2010). Moreover, other studies were carried out concerning the relationship between other polymorphisms and adverse health effects induced by Hg exposure (de Marco et al 2011;Echeverria et al 2010;Heyer et al 2009). The GST genes, especially GSTM1 (mu) and T1 (theta), are important since they present a deletion that results in impaired catalytic activity associated with greater sensitivity to toxic compounds.…”
Section: Gst Polymorphisms and Methylmercury Metabolism 961mentioning
confidence: 99%
“…Several GSH-related enzymes are highly polymorphic, and epidemiological studies demonstrated that these polymorphisms may affect the metabolism of Hg (Goyer and Clarkson 2001;Gundacker et al 2010). Moreover, other studies were carried out concerning the relationship between other polymorphisms and adverse health effects induced by Hg exposure (de Marco et al 2011;Echeverria et al 2010;Heyer et al 2009). The GST genes, especially GSTM1 (mu) and T1 (theta), are important since they present a deletion that results in impaired catalytic activity associated with greater sensitivity to toxic compounds.…”
Section: Gst Polymorphisms and Methylmercury Metabolism 961mentioning
confidence: 99%
“…In this study, MECT treatment produced a significant effect on the scores of total and individual factors of the HAMD, a scale that is indicative of depression and a guide to assess recovery. Catechol O-methyltransferase (COMT) is the main enzyme involved in the catabolism of endogenous catecholamine such as adrenaline, noradrenaline, and dopamine [20,22,23,25]. The role of COMT in the occurrence and development of various neuropsychiatric disorders such as migraine, Parkinson's syndrome, and schizophrenia has been recognized [8,19].…”
Section: Discussionmentioning
confidence: 99%
“…Individuals with double allelic substitution in the COMT gene have been shown to exhibit increased mood symptoms compared to those with no substitution [23].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moving away from epigenetic considerations, Callaghan et al [1] [4][5][6][7] . Using neurobehavioural testing, low-level mercury exposure was seen to be independently significantly associated with deficits in manual coordination skills [4] .…”
mentioning
confidence: 99%